Analysis of wave generated at the bow of catamaran hulled boat for jet ski attachment using Ansys Fluent / Muhammad Harith Ikhwan Soufei - Soufei, Muhammad Harith Ikhwan (2023)
This project will develop the combination of the jet ski at the front of the boat. The problem statement for this project is to stimulus and analyse the fluid flow created by the combination jet ski at the front which is catamaran hull. However, this design is improved from the current boat which is wave boat that the attachment of jet ski at the back of the boat, but for this project the attachment of the jet ski will be at the front of the boat because it will be easy for the driver to manoeuvring the jet ski and will unblock the view of the driver. This design also will improve from the monohull design into the catamaran hull design. This project will study the interaction of the fluid with the attachment of the jet ski of the model. The problem for this project to find the interaction of the fluid with the combination of the boat in term of resistance, contour velocity by using an Ansys Fluent Software. There are some objectives for doing this project which are to design the combination jet ski at the front of boat using the computer aided Design (CAD). Other than that, to simulate and analyse the fluid flow created by the combination jet ski at the front, which is catamaran hull using Fluid Simulation Software, Ansys Fluent. The result for this project that gets from the Computational Fluid Dynamic, Ansys Fluent which are achieve for the calculation of resistance of the model, the velocity contour of the model and the vector distribution of the model. From this project, can conclude that the higher the speed, the higher the resistance of the interaction between model and fluid. For the contour velocity that get from the result are when speed is higher the contour will provide red colour of contour while when the speed in intermediate the colour of contour is green and yellow colour. From this project also show the movement of the fluid from the inlet through the outlet. In conclusion, Computational Fluid Dynamic (CFD) can help to analyse and stimulus the resistance, velocity contour distribution and vector distribution between the fluid and the hull. Computational Fluid Dynamic (CFD) has become aa valuable tool for engineering in the design and analysis of marine system.